The Utilization of Leaves Extract and Senggani Fruit (Melastoma candidum D. Don) as an Interester of Bacterial Growth - Risnayanti, Risnayanti (Journal of Biological Science and Education, 2020)
Senggani is a plant from the Melastomataceae family and the genus Melastoma. This study aims to determine the effect and the best concentration of Senggani (Melastoma candidum D. Don) leaf and fruit extracts to suppress the growth of Escherichia coli and Staphylococcus aureus. The research design refers to the experimental research design. The independent variable (X) is Senggani leaf and fruit extract with a concentration of 1%, 5% and 10%, the total treatment in this study was 6 treatments so that the total treatment of the tested bacteria was 36 experimental units. The dependent variable (Y) is the inhibition of bacterial growth. The research method used a completely randomized design. The data analysis technique used was descriptive analysis and analysis of variance at the 95% confidence level and the LSD further test at the 95% confidence level. The results of the study concluded that (1) there was a significant effect on the concentration of Senggani (Melastoma candidum D. Don) leaf and fruit extract as a growth inhibitor for Escherichia coli and Staphylococcus aureus (2) Senggani (Melastoma candidum D. Don) leaf extract with a concentration of 10% was the best treatment to inhibit the growth of Escherichia coli and Staphylococcus aureus (3) The highest average diameter of the inhibition zone in E. coli given Senggani (Melastoma candidum D. Don) leaf extract with a concentration of 10% was 11.17 mm (4) The highest average diameter of the zone of inhibition in Staphylococcus aureus given Senggani (Melastoma candidum D. Don) leaf extract with a concentration of 10% was 10.16 mm.Keywords: Â Senggani, Melastoma candidum D. Don, Antibacterial Activity